Pengaruh Komposisi Serat Pada Komposit Berbahan Filter Puntung Rokok Dan Serat Sabut Kelapa Terhadap Penyerapan Suara - Giri Putra, I Nyoman Naya; Suardana, Ngakan Putu Gede; Kencanawati, Cok Istri Putri Kusuma (Teknik Desain Mekanika; Vol 11 No 2 (2022): April 2022 : Teknik Desain Mekanika, 2022)
Abstract Indonesia is the fourth most ipopulous countryi in the worldi. The density of population in Indonesia, resulting in many active smokers in Indonesia, which reached up to 31.44% of smokers in Indonesia in 2020. The cigarette industry in Indonesia is quite large, with excise income from cigarettes up to 96%. The researcher did an alternative that can be utilized to manage the cigarette filter waste by diluting it with 100% purity acetone. The dissolve cigarette filter will be used as a matrix material in a composite with coconut fiber which is applied as sound absorption. The composite that has been made used the volume fractions of 0%, 10%, 20%, 30%, and 40% fiber. The process of making composite used ASTM E 1050-98 as a reference. Testing the sound absorptioni coefficienti usingi the impedance tube method. The lowest sound absorptioni coefficienti is found in the 0% fiber specimen which at each frequency produced a sound absorption coefficient of not more than 0.1. While thei largesti soundi absorptioni coefficient is found in the 40% specimen at the frequencyi of 4000i Hzi with a sound absorption coefficient of 0.5. The characteristic of composites and fiber-matrix mixtures could be seen from the results of morphological tests through micro-photographs. Keywords: composite, sound absorption, cigarette filter, coconut fiber, sound absorption coefficient test